Rock powder and organic fertilization in soil cultivated with black bean - Gotz, Lenir Fátima; Piovesan, Felipe; Castamann, Alfredo (Scientia Agraria Paranaensis, 2020)
The use of rock powder as a source of nutrients to plants can be an alternative or complement to mineral soluble and organic sources. Thus, the aim of this study was to evaluate the potential of different rock powder doses, associated or not with livestock manure, as a source of nutrients for bean and its effect on soil chemical attributes. The treatments consisted of the application of 0, 3, 6, 9 and 12 Mg ha-1 of rock powder, associated or not with livestock manure (17 Mg ha-1), applied on the soil surface, without incorporation. The experiment was carried out in completely randomized blocks, with three replicates, and in a factorial arrangement (5x2). The grain yield of bean, height plants and number of plants m-2 were not influenced by the treatments. On the other hand, the application of 3 Mg ha-1 of rock powder associated with livestock manure resulted in a higher number of grains per pod, and the increase in the rock powder doses affected the number of pods per plant. In the soil, only the manure application, regardless of the rock powder, resulted in effects: reduced potential acidity and potential cation exchange capacity, and increased phosphorus content and base saturation. Thus, rock powder, associated or not with livestock manure, is not effective in improving bean yield and soil chemical attributes after approximately three months of application, and the use of livestock manure, regardless of the rock powder doses, improves some chemical attributes in the soil.